Design and validation of the pseudoscientific thinking scale - Jaimes Alvarez, Freddy (2023)
The objective of this research was to design and validate a pseudoscientific thinking scale. The study is of an instrumental type, whose sample consisted of 686 Peruvian adult participants (42% women). Regarding construct validity, an exploratory (EFA) and confirmatory (CFA) factor analysis were performed; and for reliability evidence, McDonald’s omega coefficient was used. The results of the EFA showed a unidimensional model of 8 items. The CFA presented an adequate fit, c2(20) = 35.5, CFI = .995, RMSEA = .047, SRMR = .026, TLI = .994 thus confirming the one-dimensional structure with factor loadings between the values of l = .68 and l = .86 (w = .92). Finally, the academic and social implications of this new psychometric instrument are discussed.